Oral Health-Related Quality of Life among Children Aged 11-14 Years Old with and without Parental Care in South-East of Iran - Homa Kamyabi; Mohammad Amin Darijani; Sara Amanpour; Vahid Yazdi-Feyzabadi; Rahim Fereidooni; Sorena Fardisi (Association of Support to Oral Health Research (APESB), 2023)
Objective: To measure the Oral Health-Related Quality of Life (OHRQoL) and compare children with and without parental care. Material and Methods: This cross-sectional study was conducted on 160 schoolchildren with parental care and 100 orphans in Kerman, Iran. After fulfilling the questionnaire voluntarily, a clinical examination was performed, and indices such as decayed, missing, and filled teeth (DMFT), molar-incisor hypoplasia (MIH), modified gingival index (MGI), traumatic dental injury (TDI), and malocclusion were recorded. Data were statistically analyzed using SPSS version 25 via the ANOVA, Pearson's correlation coefficient test, Chi-Square test, and descriptive statistics. Results: Children without parents scored poorly for OHQRoL items compared to those with parents (p<0.001). DMFT was not significantly related to OHRQoL; however, missing teeth were correlated with the CPQ11-14 overall. Also, the TDI index had a significant relationship with CPQ mean score (p=0.02). Moreover, the difference in the mean CPQ11-14 score in children with TDI in the two groups was significant regarding the quality of life (0.031). Conclusion: OHRQoL differed significantly between children in the two groups, which can be influenced by gender and habits. Due to the vulnerability of welfare-supported children without parental care, these findings emphasize the value of preventive and health-promoting measures for this group of children.